Strabismus Measurements Using the Alternating and Simultaneous Prism Cover Tests: Doi: 10.36351/pjo.v40i2.1763 - Azam, Shua (Pakistan Journal of Ophthalmology, 2024)
Purpose: Tocomparetheangleofdeviationbyperformingsimultaneousprismcover test (SPCT) and alternate prism cover test (APCT) at near (33cm) and far (6m). Study Design: Cross-sectional observational. Place and Duration of Study: Al-Ibrahim Eye Hospital, Karachi from July 2021 to December 2021. Methods: This study enrolled 32 participants diagnosed with constant esotropia, aged between 5 and 25 years, comprising 14 males and 18 females. Comprehensive ocular examinations for strabismus were performed, including simultaneous prism cover tests at both distance and near fixation, conducted with and without corrective glasses. Subsequently, an alternate prism cover test was administered at each fixation point, again both with and without glasses. Binocular single vision was evaluated using the Worth Four Dot test and the 10Δ test. Statistical analysis was conducted using SPSS version 20.0. Results: At distance fixation, the mean deviation angle measured by the simultaneous and alternate prism cover tests exhibited a significant difference of 9.78Δ (p=<.001). Similarly, at near fixation, the mean deviation angle between the simultaneous and alternate prism cover tests showed a significant difference of 10Δ (p=<.001). Conclusion: This study demonstrates a notable and statistically significant variance in the measured angle of deviation when employing different testing methodologies (SPCT and APCT).